Innovative roller-based physical fitness training media for enhancing motor skills in children with special needs - Simatupang, Nurhayati; Sinulingga, Albadi; kasih, Indra; Daulay, Dicky Edwar; Siregar, Samsuddin (Edelweiss Applied Science and Technology, 2024)
This study aims to evaluate the quality of roller-based physical fitness training media for children with special needs. This research was conducted at the State University of Medan, Faculty of Sports Science, in the Sports Science study program. The data collection was carried out using expert test sheets and questionnaires. This evaluation involved learning media experts, fitness experts, and language experts. In addition, this study also involved students to measure the practicality of the developed training media. This study found that the roller-based physical fitness training media for children with special needs, which were developed based on the results of expert tests, had met the criteria for training media, learning media, fitness training, language, and practicality. This can be seen from the results of the expert test, which showed that after going through two tests and one revision, the developed training media obtained a score of 90% for fulfilling media criteria, 95% for fulfilling learning media criteria, 91% for fulfilling fitness training criteria, 91% for fulfilling language criteria, 90% for fulfilling practicality criteria. Based on these results, it can be concluded that the developed roller-based physical fitness training media is ready to be used.